Nutritional status and food safety in teenage pregnant women. Pereira, Colombia, 2009 - Quintero Tabares, Rocío; Muñoz Astudillo, Ma Nelcy; Álvarez Sierra, Luz Elena; Medina Perea, Gloria Amparo (Investigación y Educación en Enfermería, 2010)
Objective. To assess the nutritional status and food safety perception of teenage pregnant women consulting in institutions from the ESE Salud Pereira during the year of 2009. Methodology. Descriptive transversal cut study. With a 95% confidence interaRTval, a sample of 150 pregnant women from the prenatal control assistants between April and June of 2009 were chosen. Four professional nurses were trained as interviewers. A survey and the Latin-American and Caribbean food security scale were applied. Nutritional assessment was performed from the biomarkers, anthropometric and obstetric indicators registered in the clinical history. A single variable and bivariate analysis was made. Results. 95% of the teenage pregnant women had socioeconomic status I and II, 59% hadn’t completed secondary education, 79% were primigravid, 21% had low weight before pregnancy and 45% low weight during pregnancy. 15% showed anemia. 33% reported urinary tract infection. 8.7% had PIH. 63.3% of the pregnant women perceived any degree of food insecurity which was severe in 22.7% of the homes. Conclusion. A high low weight before pregnancy ratio no opportunely compensated was found. Due to the food security impact over nutrition in pregnancy it’s monitoring should be included as one of the basic activities in the prenatal attention.